A homologue gene of β-catenin participates in the development of shrimps and immune response to bacteria and viruses. Issue 1 (November 2015) - Xie, Ya-Kai; Ding, Ding; Wang, Hui-Min; Kang, Cui-Jie
Abstract: β -Catenin is a multifunctional protein that is involved in many physiological processes, including development, cell proliferation, cell migration, and apoptosis. However, the function of β -Catenin in crustacean is unknown. In this study, the first shrimp homologous gene of β - catenin in Marsupenaeus japonicus (i.e., Mjβ-catenin ) was identified and characterized. The full-length of the complementary DNA of Mjβ-catenin is 3130 bp, including a 2463 bp open reading frame that encodes 821 amino acid. Multiple alignment of β -Catenin proteins suggested that the Armadillo/ β -Catenin-like repeat domains were conserved. Phylogenetic analysis showed that β -Catenin from shrimp was clustered into one group with invertebrate β -Catenin. The transcription of β - catenin in various development stages of shrimp was detected and persistently increased as the shrimp matured. In adult shrimp, β - catenin was widely distributed in detected tissues and has the relatively high expression level in gills, hemocytes, testes, and ovaries. The transcripts of β - catenin in tissues of adult shrimp were significantly up-regulated at various time points after infecting with Staphylococcus aureus, Vibrio anguillarum, and white-spot syndrome virus. Furthermore, knockdown of β - catenin resulted in impaired bacterial clearance ability and increased virus copy in shrimp in vivo . Therefore, β -Catenin in shrimp participates in the development and immune response of shrimps. Highlights: A homologous gene of β - catenin was cloned from shrimp Marsupenaeus japonicus. β-Catenin was persistently expressed during shrimp development. β-Catenin knockdown led to imperfect bacterial clearance ability in vivo . β-Catenin participated in the anti-WSSV immunity of shrimp.